Polymers based on phenyl methacrylate: Synthesis via atom transfer radical polymerization, characterization, monomer reactivity ratios and thermal stabilities - Demirelli, K; Kaya, E; Coskun, MC (Wiley, 2006)
The atom transfer radical copolymerization of phenyl methacrylate (PMA) with methyl methacrylate (MMA) was performed in bulk at 110 degrees C in the presence of ethyl 2-bromoacetate, cuprous bromide (CuBr), and 2,2'-bipyridine. Also, free-radical copolymerization of PMA with MMA was carried out in the presence of 2,2'-azobisisobutyronitrile in 1,4-dioxane solvent at 60 degrees C. The copolymers were characterized by IR, H-1 NMR, and C-13 NMR techniques. The compositions of the copolymers were determined from the H NMR spectra. The in situ addition of ethylmethacrylate to a macroinitiator-poly(phenyl methacrylate)[M, = 10,560, M-w/M-n = 1,68]-afforded an AB-type block copolymer. The molecular weight and molecular weight distribution were obtained using gel permeation chromatography (GPC). The polydispersities for the living copolymer (48 mol % PPMA units) and the free-radical copolymer (42 mol % PPMA) were 1.43 and 2.40, respec-tively. For the two copolymerization systems, the monomer reactivity ratios were obtained by using both Kelen-Tudos and Fineman-Ross equations. The initial decomposition temperatures of the resultant copolymers decreased with increasing mole fraction of PMA, which indicate that heat resistance of copolymer improved by decreasing the PMA units. Blends of poly(PMA) and poly(MMA) obtained via ATRP method were prepared by casting films from dichloromethane solution. The blends were characterized by differential thermal analysis or differential scanning calorimetry and thermogravimetry. The results were comparable with each other. (c) 2006 Wiley Periodicals, Inc.
Keywords: ATRP; blend; thermal analysis; monomer reactivity ratios